Artikel Massage Training For Blind At "Tuah Sakato" Bina Netra Social Home In Padang - Masrun Masrun; M Ridwan (Jurnal Berkarya Pengabdian Masyarakat, 2021)
Decent work and a living for humanity are part of human rights for everyone, including Persons with Disabilities, such as blind. At the 1945 Constitution provides legal guarantees and protection for its implementation. The problem is the discriminatory attitude towards persons with disabilities and the low level of education of persons with disabilities as a gap between persons with disabilities and non-disabled workers. The Bina Netra Social Institution "Tuah Sakato" Padang, is an institution that participates in providing guidance related to people with disabilities, especially the visually impaired. At the Bina Netra Social Institution "Tuah Sakato" Padang, there are not many hard skills and soft skills activities, which are the provisions for blind people, especially in massage training. Massage training is a solution to open up job opportunities for blind people, so t they can be independent in generating income for themselves and their families.